The Main Requirements of the Law to the Verdict of the Court - Airapetean, Artur (Acta Universitatis Danubius. Juridica, 2021)
The obligatory reference in the decision to its legal basis forces the decision maker to actively use legal information, carefully familiarize himself with the current legal acts, the guiding resolutions of the Plenum of the Supreme Court of Justice. The need for normative justification strengthens the rule of law, raises the legal culture of all legal proceedings. Exact adherence to the law when making a decision and the requirement of normative validity of decisions are an important guarantee against abuse of power and official position, against the manifestation of subjectivism.